Review on Aerodynamic Characteristics of Helicopter Tail Rotor Propeller Using Quasi-Continuous Vortex Lattice Metho - Koto, Jaswar; Ammoo, M.S; Ishak, I.S.; Firdaus, Firdaus; Nofrizal, Nofrizal (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
This paper reviews on application of quasi continuous vortex lattice method for determining the performance of helicopter tail rotor propeller. Tail rotor blade for Bell B206 of one seat helicopter is used. The method is developed to be suitable for analyzing the performance of propeller in term of thrust, torque, and efficiency. These parameters are calculated based on pressure on blade.